2017
DOI: 10.1021/acs.orglett.7b00887
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid-Mediated Hydrofluorination of o-Azaxylylenes Derived from 3-Bromooxindoles

Abstract: The hydrofluorination reaction of 3-bromooxindole using mild HF reagents in an ionic liquid is described. This transformation can operate at room temperature to give a series of 3-substituted 3-fluorooxindole derivatives including racemic BMS 204352 (MaxiPost). The mechanistic study about interactions between HF and 3-butyl-1-methylimidazolium tetrafluoroborate [bmim][BF] is also discussed on the basis of energy calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…α‐Dialkyl bromides showed good reactivity to deliver sterically hindered fluorides 26 – 32 in high yields. We previously reported ionic liquid‐mediated hydrofluorination of o ‐azaxylylenes derived from 3‐bromo‐oxindoles [13h] . In this study, the 3‐bromo oxindole derivative was treated with AgF; then, the corresponding product ( 33 ) was isolated in 28 % yield.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…α‐Dialkyl bromides showed good reactivity to deliver sterically hindered fluorides 26 – 32 in high yields. We previously reported ionic liquid‐mediated hydrofluorination of o ‐azaxylylenes derived from 3‐bromo‐oxindoles [13h] . In this study, the 3‐bromo oxindole derivative was treated with AgF; then, the corresponding product ( 33 ) was isolated in 28 % yield.…”
Section: Resultsmentioning
confidence: 96%
“…To overcome these intrinsic drawbacks, we focused on generation of electrophilic o ‐azaxylylene intermediates derived from 3‐bromo‐oxindoles with nucleophilic fluoride transfer to form sp 3 C−F bonds (Figure 1 B). [13h] However, this method did not apply to linear α‐bromoamides. Herein, we disclose silver‐promoted nucleophilic fluorination reactions of α‐bromoamides under mild conditions, providing access to primary, secondary, and tertiary fluorides in high yields (Figure 1 C).…”
Section: Introductionmentioning
confidence: 99%
“…Some control experiments were conducted in order to elucidate the mechanism. Previous reports [ 58 , 59 , 60 , 61 , 62 ] have suggested that a radical process was involved in iodide/oxidant catalyzed C-N bond formation. However, when a stoichiometric amount of radical inhibitors, like TEMPO, BHT and hydroquinone, was used, the cyclization of 1a proceeded smoothly and afforded the desired product 2a in comparable yields ( Scheme 4 ), indicating a complete different pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the catalytic system with I − or I 2 and a terminal oxidant has emerged as an environmentally benign oxidative system for a range of transformations, such as etherification, lactonization, and others [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Based on our continuing interest in the synthesis of 2-oxindole derivatives and the application of iodine/iodide catalysis [ 52 , 53 , 54 , 55 , 56 , 57 ], we herein report our progress in the TBAI/H 2 O 2 catalyzed intramolecular oxidative amination of 3-aminoalkyl 2-oxindoles to give 3,2′-pyrrolidinyl-spirooxindoles and their 6/7-membered analogs [ 58 , 59 , 60 , 61 , 62 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquids (ILs) have received great attention due to their low melting point, high ionic conductivity, high chemical and thermal stability, and extensive solubility [18]. Furthermore, the unique structure and ionic interaction in ILs endow them with unique physical and chemical properties, which have been widely applied in organic synthesis [19], extraction [20] and catalysis [21]. In inorganic synthesis, various nanomaterials, presenting well-defined shapes and sizes and superior performance, have been successfully prepared, in which ILs play irreplaceable roles [22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%